Blue Economy threats, contradictions and resistances seen from South Africa - Patrick Bond (Journal of Political Ecology, 2019)
South Africa hosts Africa's most advanced form of the new Blue Economy, named 'Operation Phakisa: Oceans.' In 2014, the McKinsey-designed project was formally launched by now-disgraced President Jacob Zuma with vibrant state and corporate fanfare. Financially, its most important elements were anticipated to come from corporations promoting shipping investments and port infrastructure, a new generation of offshore oil and gas extraction projects and seabed mining. However, these already conflict with underlying capitalist crisis tendencies associated with overaccumulation (overcapacity), globalization and financialization, as they played out through uneven development, commodity price volatility and excessive extraction of resources. Together this metabolic intensification of capital-nature relations can be witnessed when South Africa recently faced the Blue Economy's ecological contradictions: celebrating a massive offshore gas discovery at the same time as awareness rises about extreme coastal weather events, ocean warming and acidification (with profound threats to fast-bleaching coral reefs), sea-level rise, debilitating drought in Africa's main seaside tourist city (Cape Town), and plastic infestation of water bodies, the shoreline and vulnerable marine life. Critics of the capitalist ocean have demanded a greater state commitment to Marine Protected Areas, support for sustainable subsistence fishing and eco-tourism. But they are losing, and so more powerful resistance is needed, focusing on shifting towards post-fossil energy and transport infrastructure, agriculture and spatial planning. Given how climate change has become devastating to vulnerable coastlines – such as central Mozambique's, victim of two of the Southern Hemisphere's most intense cyclones in March-April 2019 – it is essential to better link ocean defence mechanisms to climate activism: global youth Climate Strikes and the direct action approach adopted by the likes of Dakota Access Pipe Line resistance in the US, Extinction Rebellion in Britain, and Ende Gelände in Germany. Today, as the limits to capital's crisis-displacement tactics are becoming more evident, it is the interplay of these top-down and bottom-up processes that will shape the future Blue Economy narrative, giving it either renewed legitimacy, or the kind of illegitimacy already experienced in so much South African resource-centric capitalism.